Hot water a novel (New York Vanguard Press, 2011)
"Environmental activist AJ Palladino, first encountered in Rock Bottom, is no stranger to the juggling act of managing both work and family. But when she?s asked to leave home and take a case involving a nuclear power plant, it takes all her skills to keep her world from crashing down on her. Colleton River is a new one-of-a-kind nuclear facility designed to create medical isotopes with the potential to save millions of lives. Unfortunately, the plant has been plagued by a series of mishaps that, despite several investigations, have remained unexplained, other than plain old bad luck. The accidents have caused the locals to protest the plant while drawing the attention of an anti-nuclear protest group as well as several home-grown terrorists who sense an opportunity to sow fear and chaos. Owen Grandel, Colleton River?s owner, travels from South Carolina to West Virginia to personally ask AJ for help. AJ knows she?s going to have her hands full investigating the accidents and calming the situation at the plant. What she doesn?t foresee is her simple business trip turning into disaster when her grandmother suffers a near-fatal accident back home, her parents are deemed unfit to watch her son, and, after an approaching hurricane traps AJ in South Carolina, her son disappears. Things really heat up when she discovers the cause of the "accidents" and learns that the plant is hurtling towards nuclear catastrophe--with AJ stranded at ground zero. Can AJ stop the plant?s meltdown, save the community, herself, and her family in time?"--Provided by publisher.
Keywords: Families -- Fiction; Nuclear facilities -- Accidents -- Fiction; Suspense fiction; Women environmentalists -- Fiction; Single mothers -- Fiction